Apilamätä apilan talvehtimisen heikentäjänä Suomessa - Ylimäki, Aarre (Agricultural and Food Science, 1969)
Material on the distribution and damage of clover rot was collected in the years 1946—1965 during journeys in different parts of the country and through inquiries made by letter. A total of 392 Sclerotinia trifoliorum samples from an area of 91 communes (Figure 3) were collected and cultivated. The material indicates that the fungus is spread over all the most important areas of red clover cultivation. Notes on the overwintering of cultivated plants and meteorological observations during 20 years in Tikkurila (Tables 1 and 2) show that the occurrence of clover rot epidemics mainly depends on the climatic conditions of the autumn and on the humidity of the vegetation layer. The direct significance of the temperature is evidently smaller, cold however stops the epidemic, as the relative humidity of the air becomes too low for the fungus. During a long, rather mild autumn, the damage caused by clover rot can be considerable as is indicated by the control trials. It has been observed that clover rot spreads and attacks clover plants even at a temperature of 0°C which is far below the optimum temperature of the growth of the mycelium of the fungus. Apothecia seem likewise to develop in a wide temperature range, though they do not tolerate frost. The slow melting of the snow in spring increases the humidity on the surface of the soil and promotes the damage by clover rot. The differences in the isolates of S. trifoliorum in regard to their pathogenicity were so significant that they can be considered as being different biotypes of the fungus. On the other hand the pathogenicity of different isolates and the susceptibility of the different clover varieties to disease seem to a great extent to be the functions of time (Fig. 4 and 5). The differences in clover varieties in their resistance to disease, are thus based on their ability to delay the domination of the disease rather than on real resistance. In Finland there are many local red clovers which are a result of long-term adaption and may prove valuable as breeding material. A number of clover rot control experiments with PCNB or quintozene preparations were carried out on grasslands in different parts of the country in the years 1946—1965. Because the abundance of clover rot varies, both annually and locally and because control treatments have been carried out in many different ways, the results of the control experiments also vary. With two mowings the increase of the fresh yield of all the 145 treatments was approx. 41 %. With one mowing the increase of dry hay in 186 treatments was approx. 26 % (Table 4). Of all the treatments about one half has given an increase of fresh yield of not below 21 % after two mowings and nearly a quarter of an increase in the dry hay yield amounting not less than 21 % after one mowing (Table 5). The success of the control depends decisively on the time it is started. The control should start before the clover rot has become dominant. Because the outbreak and spread of the disease takes place only when the relative humidity in the vegetation layer is very high, the time chosen for the control should be based on the conditions of humidity in the autumn. When the early autumn has been less rainy, only one control treatment has been sufficient in October—November, even if a more certain result is obtained with 2—3 treatments during the autumn. In practice it is evidently appropriate to carry out the first control treatment at the end of September the beginning of October if the autumn is rainy, and to repeat it after about one month. If the early part of the autumn is dry, only one treatment is needed approximately at the end of October early November. 5—6 kg/ha has proved to be a sufficient amount of effective substance (PCNB). Additional substance may sometimes give a more complete control result, but the difference is so small that it does not always equal the extra cost involved. Better results have been obtained with sprays than with dusts owing to the fact that it is easier to apply sprays than dusts evenly, apart from that the forms of usage have not been significant. Because the damage of clover rot is generally greatest in first year leys, they have also yielded the best control results. In these experiments it has been established that the treatment has also aftereffects in the following years (Table 7). It appears that the control has indirectly prevented the weeding of grasslands, which especially on clover seed cultivations is of major significance. The control method with PCNB may be used e.g. in variety and other trials of clover to distinguish clover rot from other factors lowering the overwintering (Tables 8—10, Fig. 8).